Metallurgical investigations of laser remelted additively manufactured AlSi10Mg parts: Metallurgische Untersuchungen von laserstrahlumgeschmolzenen additiv hergestellten AlSi10Mg Bauteilen. Issue 5 (May 2017) - Schanz, J.; Hofele, M.; Ruck, S.; Schubert, T.; Hitzler, L.; Schneider, G.; Merkel, M.; Riegel, H.
Abstract: Selective laser melting is gaining importance to manufacture reliable and highly complex parts. However, the surfaces of the selective laser melted parts exhibit for many applications an insufficient high roughness, thus require subsequent post processing steps. A relatively new way to reduce the surface roughness is the laser polishing technique. In the present paper, additively manufactured AlSi10Mg samples were polished with different laser intensities and laser modes. The investigations contain the potential of roughness reduction and enhancement of the surface appearances, which can be achieved by laser polishing of the as‐built surfaces. An initial arithmetic mean roughness of 8.43 μm was remarkably reduced up to 98 %. The compositions of the polished surfaces were detected and the surface appearances were examined. Reasons and mechanisms were explained and depicted for the occurred shade formations on the polished surfaces. High laser intensity led to segregation of silicon and magnesium on the surface. A higher laser intensity enabled an increased melt depth within the conture layer of the selective laser melting structure. Through increasing melt depth, a porosity of max. 1.7 % was detected in the remolten area. Hardness investigations of the initial and laser remolten cross section revealed no significant reduction in hardness.